PERAN ORANG TUA DALAM MENDIDIK AKHLAK ANAK USIA 9-12 TAHUN DI DUSUN BINDANG DESA KARTIASA TAHUN 2023 - Suhana; Rusiadi; Saripah (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The aim of this research is to reveal the morals of children aged 9-12 years, especially in Bindang Hamlet, Kartiasa Village. Parents also use several methods to educate children's morals. This research is descriptive qualitative in nature and uses data collection techniques by interviews, observation and documentation. The results of the research show: 1. Children's morals are polite and respect their elders and there are also children who like to say bad things to friends and other people; 2. Parents' method of educating children's morals is by using the Advice Method, Habituation Method, and Exemplary Method; 3. Factors inhibiting parents from educating children's morals are negative relationships at home, lack of parental attention to children, and technology. Supporting factors include support from family and a good environment.